Achieving effective patient and public involvement in international clinical trials in neurology. Issue 3 (June 2020) - Tallantyre, Emma C.; Evangelou, Nikos; Bale, Clare; Chaudhry, Burhan Z.; Gray, Emma H.; LaRocca, Nicholas; Pavitt, Sue; Miller, Deborah M.; Planchon, Sarah M.; Ontaneda, Daniel; Manzano, Ana
Abstract : There is a growing need for patient and public involvement (PPI) to inform the way that research is developed and performed. International randomized controlled trials are particularly likely to benefit from PPI, but guidance is lacking on how or when it should be incorporated. In this article, we describe the PPI process that occurred during the design and initiation of an international treatment clinical trial in MS. PPI was incorporated using a structured approach, aiming to minimize bias and achieve equivalence in study design, implementation, and interpretation. Methods included PPI representation within the study research team, and the use of focus groups, analyzed using thematic framework analysis. We report the outcomes of PPI and make recommendations on its use in other neurology clinical trials. By sharing our model for PPI, we aim to maximize effectiveness of future public involvement and to allow its effect to be better evaluated.